A caveat to common hemicyanine dye components and their resolution. Issue 51 (26th May 2020) - Park, Hyeon Jin; Song, Chang Wook; Sarkar, Sourav; Jun, Yong Woong; Reo, Ye Jin; Dai, Mingchong; Ahn, Kyo Han
Abstract : Hemicyanine dyes containing typical heterocycles such as 2-indolinium have limited chemo- and photo-stability issues, which can be resolved with a 4-pyridinium derivative that also shows good two-photon imaging capability. Abstract : Near-infrared-emitting hemicyanine dyes are widely used in activatable fluorescent probes for various biological analytes; however, they are chemically unstable and show photoinstability, as shown here with naphthalene-based hemicyanines containing a typical hemicyanine moiety, 2-indolium. These issues can be resolved with a 4-pyridinium derivative, which also has good two-photon imaging capability.